Physical frailty related to cognitive impairment and COPD exacerbation: A cross-sectional study. (March 2023) - Tsai, Chen-Liang; Chang, Wen Pei; Lin, Yen-Kuang; Ho, Shu-Chuan; Lin, Yu-Huei
Highlights: In this study, we observed that frailty is highly prevalent among COPD patients, is associated with mild cognitive impairment (MCI). . Except for naming, COPD patients with frailty had worse cognition in attention, language, abstraction, delayed recall, orientation, and visuospatial executive domains. Frailty is common among COPD patients and has been associated with exacerbated frequency; therefore, identifying frailty can assist in recognizing patients and selecting the optimal action plan for improved clinical outcomes.